Spontaneous urinary bladder perforation as a cause of recurrent, progressive ascites with multiorgan dysfunction syndrome (Indian Journal of Case Reports, 2018)
Spontaneous rupture of the urinary bladder wall is a rare complication that may lead to intraperitoneal accumulation of urine and is mistaken for ascites from other causes. This often leads to repeated and inconclusive diagnostic tests. Here, we report the case of a 60-year-old female, with a past history of cervical cancer, who presented with recurrent episodes of pain abdomen and breathlessness over 1 year period. She was hospitalized multiple times and found to have ascites. Ultrasound and computed tomography scan of the abdomen along with an ascitic fluid analysis were done at each admission, which were inconclusive as to the cause of the ascites. A diagnostic laparoscopy to rule out peritoneal metastases showed perforation of the urinary bladder wall with intraperitoneal urine leakage. Bladder wall repair was done the following which the patient recovered uneventfully.